Determining and meeting the educational needs of students and urban gardeners and farmers on urban soil quality and contamination topics - Harms, Ashley Marie Raes (Kansas State University, 2011)
Interest and participation in urban agriculture is growing in many cities throughout the United States. Urban gardeners and farmers produce food on various types of urban lands. Common soil contaminants of urban areas limit the amount of land on which food may safely be grown. The objective of this study was to assess and meet the informational and technical assistance needs of urban gardeners and farmers as well as students enrolled in the introductory soils science course at Kansas State University on the topics of urban soil quality and contamination. A needs assessment survey of urban gardeners and farmers was conducted in four communities; Tacoma and Seattle, Washington, Kansas City, Kansas and Missouri, Manhattan, Kansas, and Gary, Indiana. The survey generated information about what urban gardeners and farmers know, think they know, and want to know about urban soil quality and contamination. Eighty-eight percent of respondents indicated that they do not have knowledge of the best management practices to minimize health risks involved when growing food crops on soils contaminated with lead, cadmium, arsenic or organic contaminants. Our results suggest that urban gardeners and farmers require and want information and guidance on soil testing for common contaminants, interpretation of testing results, and best management practices for growing food on mildly contaminated soils. The students enrolled in the introductory soil science course at Kansas State University are future agricultural and environmental professionals who need skills to address urban soils issues. Most of the students in the Agronomy 305: Soils course are not Agronomy majors. Furthermore, an increasing number of Agronomy 305 students come from urban and suburban communities and/or have interest in working in urban environments upon completion of their undergraduate degree. An urban soils laboratory was developed in response to the future workforce demands as well as the demographics of students enrolled in the Agronomy 305 course. Throughout the semester students evaluated the physical, chemical, and biological properties of a soil from this urban community garden. Reaction of students to the new urban soils lab offering has been positive with 72% of students enrolled in the course reporting that they have interest and need in learning about the urban soil issues covered in the lab course. Overall, student responses about their learning experience in the urban soils laboratory course were positive, indicating that incorporating urban soil principles enhanced their soil science education. Students who participated in the urban soils lab are better prepared, as future agricultural and environmental professionals, to address the educational and technical assistance needs of urban growers.
Keywords: Urban soil; Urban agriculture; Teaching; Soil contamination; Extension; Agriculture, General (0473); Agronomy (0285); Soil Sciences (0481)